2009
DOI: 10.1002/ejic.200801030
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Spectra of Mono‐ and Dinuclear Complexes of Fully π‐Conjugated salphen Ligands Synthesized by Using 2,6‐Dihydroxynaphthalene Carbaldehydes

Abstract: A series of mono-and dinuclear zinc(II), copper(II), nickel(II), and iron(III) complexes of novel salphen ligands were synthesized and spectroscopically characterized. The mononuclear ligand (H 2 L 1 ) was synthesized from 2,6-dihydroxynaphthalene-1-carbaldehyde and an o-phenylenediamine; the dinuclear ligand (H 4 L 2 ), which was not isolated, contains a 2,6-dihydroxynaphthalene-1,5-dicarbaldimine linkage that enables extended π-conjugation over two salphen units. By means of a controlled sequence of condensa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…Upon deconvolution of the spectra with Gaussian curves, the two experimental broad absorption bands give rise to a set of three or four transitions. The high‐energy absorption bands in the range 340–399 nm are assumed to originate from intraligand π–π* transitions, and the low‐energy absorption bands in the 419–600 nm region presumably involve metal‐to‐ligand and ligand‐to‐metal charge transfer (CT) 10,13,41,42. As previously observed,13 on passing from thf to the more polar dmso, the low‐energy structures exhibit a hypsochromic shift (Table 3), characteristic of a change in the dipole moment between the ground and excited state and indicative of CT character.…”
Section: Resultsmentioning
confidence: 99%
“…Upon deconvolution of the spectra with Gaussian curves, the two experimental broad absorption bands give rise to a set of three or four transitions. The high‐energy absorption bands in the range 340–399 nm are assumed to originate from intraligand π–π* transitions, and the low‐energy absorption bands in the 419–600 nm region presumably involve metal‐to‐ligand and ligand‐to‐metal charge transfer (CT) 10,13,41,42. As previously observed,13 on passing from thf to the more polar dmso, the low‐energy structures exhibit a hypsochromic shift (Table 3), characteristic of a change in the dipole moment between the ground and excited state and indicative of CT character.…”
Section: Resultsmentioning
confidence: 99%
“…The use of 2,6‐dihydroxynaphthalene dicarbaldehyde enables the construction of formally fused salphen ligands 15. We previously investigated the relationship between the structure and spectroscopic properties of homo‐ and heterometallic dinuclear and trinuclear complexes of several fused salphen ligands in the solution state 16–18. Our results showed that the π‐conjugated system is compartmentalized by the coordination site and that the degree of compartmentalization depends on the nature of the metal ion.…”
Section: Introductionmentioning
confidence: 92%
“…The first absorption band centered in the range of 260-300 nm could be assigned to a π-π* transition of the aromatic part and n-π* electronic transitions of the nonbonding electrons of the azomethine nitrogen atoms [76]. The second absorption band in the range of 320-400 nm could be attributed to intermolecular metal-ligand interactions within the whole complex (metal-ligand (d-π*) charge transfer (MLCT band)) [77,78]. Moreover, TDDFT calculation were also performed to characterize electronic transition for the experimentally observed peaks.…”
Section: Synthesis and Spectroscopic Characterizationmentioning
confidence: 99%